Occurrence and Characterization of Salmonella Isolated from Table Egg Layer Farming Environments in Western Australia and Insights into Biosecurity and Egg Handling Practices - Hamid Reza Sodagari; Ihab Habib; Scott Whiddon; Penghao Wang; Arkan Baraa Mohammed; Ian Robertson; Stan Goodchild (Pathogens, 2020)
The aim of this study was to investigate the occurrence and distribution of Salmonella in commercial layer farming environments of 26 flocks belonging to seven egg businesses (free-range and barn-laid) in Western Australia (WA). Between November 2017 and June 2018, a total of 265 environmental samples of dust, feed, water, pooled feces, and boot swabs were tested for detection of Salmonella according to standard culture-based methods. Isolates were assayed for serovar and subtyped by multilocus sequence typing (MLST). Salmonella spp. were recovered from 35% (93/265) of all tested samples. Dust (53.8%, 28/52) and pooled fecal (54.5%, 18/33) samples provided the highest Salmonella recovery rates. Nine different Salmonella serovars were characterized across the positive (n = 93) environmental samples, of which S. Typhimurium (60/93, 64.5%) and S. Infantis (21/93, 22.5%) were the most prevalent. MLST revealed that all S. Typhimurium isolates were of sequence type ST-19. Microbiological screening of Salmonella was not routinely practiced in any of the surveyed egg businesses. Some of the egg businesses exhibited variable levels of compliance with basic biosecurity measures as well as high-risk egg handling practices. Egg businesses in WA should be encouraged to adopt a voluntary program of environmental sampling and verification testing for Salmonella. Such voluntary programs will aid in supporting solutions for the management of this pathogen in the human food chain.